EFL TEACHERS’ PERCEPTIONS OF IMPLEMENTING PRE-READING ACTIVITIES IN ONLINE READING CLASSES - Dinda Ayu Octavia Putri; Zainul Aminin (PROJECT (Professional Journal of English Education), 2022)
This research aimed to find out the teachers’ perceptions, including the kinds of pre-reading activities commonly used, the advantages of pre-reading activities, and the difficulties faced by the teachers in implementing pre-reading activities in online reading classes. This study used a descriptive qualitative method. Furthermore, open-ended questions and semi-structured interview guides were used as research instruments. The participant of this study were 8 English teachers with teaching experience ranging from 10 to 15 years from different senior high schools in Lamongan. This study revealed that the teachers commonly used online pre-reading activities: previewing, predicting, questioning, writing the reader’s experience, recognizing the text structure, reading the introduction and conclusion, semantic maps, and vocabulary familiarization. The teachers believed that it positively impacts both teachers and students in online reading classes, specifically to support the students in comprehending a text and encourage students’ enthusiasm in online reading classes. Moreover, these activities helped the teacher in delivering the primary materials. Besides, the teachers should evaluate the time management in implementing pre-reading activities in online reading classes. Keywords:  Teachers’ Perceptions, Pre-Reading Activity, Online Reading Class